Electroconductive Melt Electrowritten Patches Matching the Mechanical Anisotropy of Human Myocardium - Monaghan, Michael; Olvera, Dinorath; Sohrabi, Mina; Hendy, Gillian (My University, 2020)
Cardiac patches represent a promising strategy for the treatment of myocardial infarction (MI). Here, an electroconductive cardiac patch that conforms to the mechanics of human myocardium is fabricated. By melt electrospinning writing (MEW), it is possible to fabricate an auxetic patch that can overcome the limited range of elasticity seen in conventional square patch designs. The auxetic patches can accommodate the strains and stresses exhibited by the human myocardium during diastole and systole. It is shown that the geometry of the auxetic patches can be fine‐tuned to reflect anisotropic mechanical properties. The anisotropic ratio of effective stiffness (E1/E2) of the auxetic patches agrees with the directionally‐dependent mechanics of the heart. Furthermore, in situ polymerization of doped‐polypyrrole (PPy) on the auxetic patches confers electroconductive properties close to those reported of human myocardium. This approach demonstrates the potential use of a rational design of PPy‐coated patches for their use as cardiac patches.
PUBLISHED
Keywords: Cardiac patches; Melt electrospinning writing; Auxetic materials; Mechanical anisotropy; Electroconductive materials